Vaginal self-versus clinician sampling on cervical cancer screening: an accuracy and acceptability systematic review and meta-analysis (Revista Portuguesa de Medicina Geral e Familiar, 2025)
Introduction: Self-sampling strategies have shown promising efficacy in detecting disease, but it is still unclear whether these strategies can be implemented independently of a clinical setting in a manner acceptable to women.Objectives: This review aimed to evaluate the accuracy – non-inferiority – of human papillomavirus (HPV) detection rates between clinician-collected samples and self-sampling, and secondarily to assess the acceptability of self-sampling for cervical cancer screening.Methods: A systematic search was performed mainly from electronic databases (MEDLINE, CENTRAL, and Scopus). Studies that compared both screening methods and contained data on their accuracy and acceptability were included. Two independent researchers performed study selection and data extraction. An assessment of the risk of bias was done using the QUADAS2 and Cochrane Risk of Bias Tool. The pooled sensitivity and specificity of tests were estimated and SROC curves were built. A subgroup and sensitivity analysis were performed. RevMan5.4. and Meta-DiSc® 1.4.7. were used.Results: Sixty-seven articles were included, 47 regarding accuracy and 36 regarding acceptability, with a total sample of 18,615 women aged between 15 and 80. This study showed that self-sampling, as a screening test, has a sensitivity of 87.4% and specificity of 91.2% to detect HPV. From subgroup analysis, no significant differences were detected regarding the type of test, transport device, or HPV prevalence. Regarding acceptability, women consider self-sampling to be easy, comfortable, and non-embarrassing. 62.8% preferred collection by self-sampling.Conclusion: This way of self-sampling HPV screening proved not inferior to clinician-sampling and has good acceptability among women, making it a possible alternative or complement to conventional screening. Nevertheless, there is still low evidence regarding its feasibility and applicability, therefore the next step should focus on evaluating the cost-effectiveness of this type of screening at a national and international level.
Keywords: Human papillomavirus; Cervical cancer; Self-collection; Screening; Diagnostic testing; Acceptability